PERANCANGAN ROTARY BARREL MASS FINISHING MACHINE UNTUK NUT M5 DENGAN MEDIA ABRASIF SEKAM PADI PADA PT. X - Alby Maska Kamaludin, (2022)
The finishing process of M5 Nut in Company X still uses conventional method, by using manual hand sanding,seeing the fact that the quantity of M5 Nut required from the order are 280.000 Pcs, with the required surface roughness of 1,5 µm and the manufacturing time of 20 work days, requires a machine to help the finishing process of M5 Nut. This research resulted in the design of Rotary Barrel Mass Finishing Machine with the dimensions of 59cmx30cmx30cm with the capacity of 30 litre with the motor power of 0,75 kW, and uses rice husk as the abrasive media, the finishing process using the design of rotary barrel mass finishing machine requires 1 hour, with the surface roughness of M5 Nut 1,149 µm and the M5 Nut finishing quantity of 22.500 Pcs every work days that meets the requirements of the order. Keywords: Finishing, Finishing Machine, Mass Finishing